Jogos como estratégia para facilitar o ensino-aprendizagem de operações com números inteiros - Avello, Rosane Garcia Bandeira (2006)
The objective of this research was to investigate whether the use of games improvises the learning of calculation with whole numbers or not. In doing so, a case study based on observation was done with a sample of students of the sixth grade registered at the elementary school of “Colégio Militar de Santa Maria”. Some games made on cards comprising black or red circumferences from one to twelve were used, which have represented scores won or lost, respectively, and were recorded on forms. A wooden base with two stems, similar to the “abacus” was used, where the scores won or lost were registered by means of black or red rings. Later, this “abacus” was used for adding and subtracting operations of whole numbers. Some games of bingo made on cards were also used for each operation: addition, subtraction, multiplication, division and power of whole numbers. For this games there were rules which should be followed. Finally, a bingo was used comprising all the operations mentioned before. During the games some notes were taken based on observation, with speech register, on student’s actions and expressions, and a questionary with semi structured questions was also applied, which was answered by the students of the sample. Based on the analysis of the questionary’s answers, and from the notes, some tables were made, which have shown that the games helped in the learning of math operations of addition and subtraction of whole numbers, and raise the interest of the students of math. It was suggested to other researchers to use games to work on operations of whole numbers.